Engagement of Micro and Small Enterprises in Workplace-based Learning in South Africa - Franz, Jutta; Dulvy, Elizabeth Ninan; Marock, Carmel (Washington, DC : World Bank, 2022)
Workplace-based learning (WBL) increases the labor market relevance of skills development programs and the employability of their graduates. The advantages of WBL for enriching the learning experience and improving the outcomes of skills development, and enhancing the employability of graduates, have always been recognized in South Africa. Engaging in WBL can help micro and small enterprises (MSEs) secure skilled labor and increase their productivity. Against this background, the World Bank and the Department of Higher Education and Training (DHET) agreed to conduct a study about the involvement of MSEs in WBL in South Africa. The study intends to shed light on the constraints and opportunities for expanding WBL engagement among MSEs in South Africa, by taking stock of the current situation of MSE participation in WBL, identifying constraints, potential and key enablers, and outlining possible strategies to better engage and support MSEs in WBL. The study reviews the concept of WBL in a wider sense than is often applied in skills development debates in South Africa. Unlocking the vast potential of WBL and work experience opportunities to be offered to young South Africans by small and very small (micro) enterprises will be an important contribution to the fight against youth unemployment.